Atendimento ao cliente e sua influência na qualidade do serviço oferecido aos moradores da cidade de Xambioá/T: um estudo de caso na empresa Paulo Tácio Sousa Nunes-ME - Nunes, Paulo Tácio Sousa (Universidade Federal do Tocantins, 2020)
This work has the purpose to highlight the logistical activities of the Reseller Tácio Paulo Sousa Nunes - ME (HIPERGÁS), based on processes developed by the company. In this sense, this article aimed to identify the level of quality of service offered to the distributive logistics Reseller Hipergás, seeking to provide a satisfactory service to the residents of Xambioá / TO. As methodological procedures was held at first a bibliographic research in books, articles, websites and magazines, then the place to field research, which was developed by applying a questionnaire to the company's customers. Had still a quali-quantitaviva.Tais approach procedures made it possible to understand that the majority of customers are satisfied with the quality of service provided by Reseller, however, there are still some aspects that need to be improved, such as marketing, promotion and advertising, options machines for debit and credit card as well as the attendance of employees.